Effect of structured training program on arm dysfunction, lymphedema and quality of life after breast cancer surgery - Havva Bozdemir; Dilek Aygin (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of this study the effect of the education given according to daily living activities (DLA) model on arm dysfunction, lymphedema and quality of life in patients undergoing breast cancer surgery. Interventions/Methods: In the design of the research, a randomized controlled experimental model with recurrent measurement was used. The data were collected from 60 patients (control group: 30, Intervention Group: 30) at a teriary hospital. In Research ,Patient Information Form, SPOFIA, KATZ-DLA indeks, arm, shoulder and hand injuries scale (DASH) and quality of life scale short form (SF-36) were used. Three interviews (1st week, 1st and 3rd month) were performed after surgery with patients. Analysis of data; independent T-Test, Chi-squared and Repeated Measures ANOVA were utilized. Results: SPOFIA, DASH and KATZ, GYA scale averages decreased by the time, SF-36 were found to increase the average score. In the intervention group, the measurements of the upper arm circumference are significantly better than the control group and In terms of SPOFIA3, DASH2 and DASH3 scale averages, there is a statistically significant difference between the groups (P < 0.05). Conclusions: KATZ, SPOFIA, SF-36, DASH scale score averages were recovered as the time elapsed after the operation increased. Intervention group was found to recover more early. Implications for Practice: The education programme is effective in the prevention of arm dysfunction and lymphedema and in improving quality of life. Keywords: Breast cancer, lymphedema, daily life activity model, quality of life, Continuous...